The Moroccan agricultural workers tissue. From invisibility awareness of themselves. - Chattou, Zoubir (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The purpose of this article is to contribute to the understanding of the process which triggered the recent incidents in El Ejido (Spain). Above all, this article tries to keep the ethnic violence phenomenon within a sociological context characterized by the work exploitation of the farmer workers (most of them are Moroccans) in the Spanish intensive agriculture. It also shows the immigration experience, the deprivation in which they live and the problematic relationship between the Spanish workers and the immigrants. The Moroccan immigration in the field of agriculture has been invisible for a long time. This silence cannot remain because under it there is a social problem related to the morpholysis caused by the immigration situation and the new demands that claim for better life and work conditions. The intervention of the State, the civil society and the different social actors can replace the debate on the main issues. These issues are related to a community life with dignity and respect and it is placed far from the racism caused by passions and identities.